Effect of chronic bombesin on pancreatic size, composition and secretory function in the rat. (1987) - Stock-Damge, C; Lhoste, E; Aprahamian, M; Pousse, A
Abstract : Bombesin administered subcutaneously to rats, three times daily for four days, induces pancreatic growth at a dose of 10 micrograms/kg. Growth was characterised by an increased pancreatic weight and content in protein and RNA, accompanied by cellular hypertrophy. Chronic bombesin also enhanced the pancreatic content in chymotrypsin and to a lesser degree its contents in amylase and lipase. The volume of the secretion and the output of enzymes in response to CCK under an infusion of secretin, however, remained unchanged although the functional capacity of individual cells to secret amylase and lipase was reduced. It is concluded that chronic bombesin exerts a trophic action on the rat pancreas but decreases the sensitivity of each cell to hormonal stimulation.